Application of Generalized Cauchy Process on Modeling the Long-Range Dependence and Self-Similarity of Sea Surface Chlorophyll Using 23 years of Remote Sensing Data - He, Junyu (Frontiers in Physics, 2021)
Understanding the temporal characteristics of sea surface chlorophyll (SSC) is helpful for the marine environment managements. This study chose 10 time series of remote daily sea surface chlorophyll products from European Space Agency during the period from July 29, 1998 to December 31, 2020. The generalized Cauchy model was employed to capture the local and global behaviors of sea surface chlorophyll from a view of fractal; the fractal dimension D measures the local similarity while the Hurst parameter H measures the global long-range dependence. The generalized Cauchy model was fitted to the empirical autocorrelation function values of each SSC series. The results showed that the sea surface chlorophyll owned multi-fractal in both spatial and time with the D values ranging from 1.0000 to 1.7964 and H values ranging from 0.6757 to 0.8431. Specifically, regarding the local behavior, 9 of the 10 series have low D values (<1.5), representing weak self-similarity; on the other hand, regarding the global behavior, high H values represent strong long-range dependence may be a general phenomenon of daily sea surface chlorophyll.